Pengaruh Literasi Perpajakan dan Kualitas Pajak terhadap Pembayaran Pajak Melalui Tax Morale: Studi Kasus pada UMKM di Kabupaten Dompu - Ifan Munawir; Irwansyah Irwansyah; Firmansyah Firmansyah (AKUNTANSI 45, 2026)
This quantitative study aims to analyze the direct effects of tax literacy and tax service quality on tax payments by MSMEs in Dompu Regency, as well as the role of tax morale as a mediating variable. Using accidental sampling, a sample of 87 MSMEs registered with the Dompu Regency Cooperative Office was obtained. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via SmartPLS. The results of the analysis indicate that, directly, tax literacy, tax service quality, and tax morale have a positive and significant effect on tax payments. In addition, tax literacy and tax service quality were also found to have a significant positive effect on tax morale. However, tax literacy had no effect on tax service quality. Indirectly, tax morale significantly mediated the positive effects of tax literacy and tax service quality on tax payment compliance among these MSME operators.